2017
DOI: 10.1002/ccr3.699
|View full text |Cite
|
Sign up to set email alerts
|

A delayed presentation of homozygous protein C deficiency in a series of children: a report on two molecular defects

Abstract: Key Clinical MessagePediatric emergency visits with purpura fulminans should raise the suspicion of hereditary homozygous protein C deficiency even beyond the neonatal age. The absence of this classical finding does not role the diagnosis out as atypical presentation with isolated intraocular bleeding was observed. Premarital counseling should be offered when family history suggests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Another study in Saudi Arabia reported that intracranial bleeding was noted at a lower frequency than PF, and intracranial atrophy and fibrosis were also noted, however, blindness early in life was a common outcome [24]. A literature review of 82 patients with homozygous PC deficiency from 1984 to 2014 showed that PF occurred in 53 patients (65%), blindness occurred in 16 patients (20%) and intracranial hemorrhage occurred in 8 patients (10%) [24]. Blindness is a common manifestation of severe PC deficiency and may arise from vitreal bleeding or from retinal vein, artery or vitreal vein thromboses with retinal detachment manifesting as leukocoria or ischemic optic atrophy [25,26].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study in Saudi Arabia reported that intracranial bleeding was noted at a lower frequency than PF, and intracranial atrophy and fibrosis were also noted, however, blindness early in life was a common outcome [24]. A literature review of 82 patients with homozygous PC deficiency from 1984 to 2014 showed that PF occurred in 53 patients (65%), blindness occurred in 16 patients (20%) and intracranial hemorrhage occurred in 8 patients (10%) [24]. Blindness is a common manifestation of severe PC deficiency and may arise from vitreal bleeding or from retinal vein, artery or vitreal vein thromboses with retinal detachment manifesting as leukocoria or ischemic optic atrophy [25,26].…”
Section: Discussionmentioning
confidence: 97%
“…ICTH preceded PF in both of the affected patients. Another study in Saudi Arabia reported that intracranial bleeding was noted at a lower frequency than PF, and intracranial atrophy and fibrosis were also noted, however, blindness early in life was a common outcome [24]. A literature review of 82 patients with homozygous PC deficiency from 1984 to 2014 showed that PF occurred in 53 patients (65%), blindness occurred in 16 patients (20%) and intracranial hemorrhage occurred in 8 patients (10%) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, protein C enhances fibrinolysis by neutralizing circulating plasminogen activator inhibitor and augmenting tissue plasminogen activator activity. 20 A deficiency in protein C can increase the risk of thrombosis, and there are two types of congenital protein C deficiency: Type I, defined by reduced antigenic levels and function, and Type II, characterized by diminished function while maintaining normal antigenic levels. The Human Gene Mutation Database contains more than 390 PROC mutations, including missense, nonsense, insertion, deletion, and splicing mutations, with missense mutations accounting for over 65% of all PROC mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Total retinal detachment and a left macular hemorrhage Paysse EA [2002] [ 19 ] 1 OU Flat anterior chamber Bilateral retinal detachment, fibrotic hyaloid arteries Sirachainan N et al [2003] [ 20 ] 2 OU Preserving eye function, high myopia, cerebral palsy Park UC et al [2005] [ 21 ] 1 OU Bilateral corneal opacity, microphthalmia, posterior synechia, pupillary membrane, shallow anterior chamber Vitreoretinopathy suggesting, PHPV, intravitreal masses, funnel-shaped retinal detachment with bilateral retinal dysplasia Bilateral leukocoria, no microphthalmos, blind OU de Lemus-Varela ML [2005) [ 22 ] 1 OU Vitreous hemorrhage Douglas AG et al [2010] [ 23 ] 1 OU No red reflex OU Vitreoretinal dysplasia, severe hazy media in one eye and OU PFV Leukocoria OS, bilateral microphthalmia,, deranged VEP, poor vision, nystagmus Wang BZ [2012] [ 24 ] 1 OU Macular hypoplasia with blond retinal background Doll’s eye movements, no fix and follow movement of the eyes, ponto-cerebellar hypoplasia, nystagmus, strabismus, Flat ERG Desai S et.al. [2014] [ 25 ] 1 OU Combined central retinal venous and arterial obstruction Severe Type II protein C deficiency with factor V Leiden mutation, Glaucoma Almarzouki HS et al [2016] [ 26 ] 2 OU Peter’s anomaly Baothman AA et al [2017] [ 27 ] 5 OU Peter’s anomaly, corneal opacity (3/5) Blindness (4/5OU), ocular hemorrhage shortly after birth resulted in visual loss (1/5) Present study 1 OU Left eye shallow anterior chamber, cataract...…”
Section: Discussionmentioning
confidence: 99%